Caracterização de filmes de polietileno de baixa densidade incorporados com diferentes concentrações de montmorilonita (Research, Society and Development, 2020)
This work aimed to evaluate the effect of incorporating different concentrations of montmorillonite in low-density polyethylene films. The incorporation Cloisite® 10A nanocomposite in the films was carried out using a single screw extruder modular. After the incorporation of six concentrations of organophilic montmorillonite clay (0.5, 1.0, 1.5, 2.0, 2.5 and 3.0%, w/w) to the films, their optical, mechanical (tensile strength, elongation and Young modulus), and gas barrier (CO2) properties were investigated. The degree of exfoliation was evaluated through the analysis of X-ray diffraction. The incorporation of nanoparticles from montmorillonite increased the opacity of the films. Regarding their mechanical properties, the incorporated films with montmorillonite presented reductions in tensile strength and elongation values, whereas the modulus of elasticity did not show any significant difference. They also showed an increase in the permeability of CO2. The analysis of X-ray diffraction showed no formation of nanocomposites. It was observed, therefore, that the properties of the films were affected by the incorporation of montmorillonite clay.